2008
DOI: 10.1002/hon.862
|View full text |Cite
|
Sign up to set email alerts
|

A pilot MRI study of organ specific hemosiderosis and functional correlation in Chinese patients with myelodysplasia and aplastic anemia with raised ferritin levels

Abstract: We performed MRI and endocrine assessment in 27 adult Chinese patients with severe aplastic anemia (SAA) and myelodysplasia (MDS). Despite high ferritin levels, cardiac hemosiderosis and heart failure was not common, and were not concordant in most cases. However, significant correlation was found between cardiac T2/T2* MRI assessment, ejection fraction and ferritin levels. Furthermore, there was a high incidence subclinical pancreatic abnormality that was related to liver MRI T2* readings. Hence, chelating ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Those who become transfusion dependent can develop substantial morbidity and significantly reduced overall and leukaemia-free survival (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Those who become transfusion dependent can develop substantial morbidity and significantly reduced overall and leukaemia-free survival (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Increased iron absorption and subsequent increase liver iron has been described in 85% of patients with Hb H disease [16]. Despite high hepatic pancreatic and pituitary iron observed by MRI, cardiac hemosiderosis or overt endocrine dysfunction was uncommon [17]. A greater risk for iron-induced organ damage can be expected in Hb H-CS.…”
mentioning
confidence: 99%
“…The clinical importance of iron overload in MDS and the risk‐benefit balance of iron chelation therapy are incompletely understood and controversial topics at present [29, 30]. There have been at least three prior publications assessing cardiac iron overload measured noninvasively using newer T2*/R2* MRI techniques in heavily transfused MDS populations, and these three studies all suggested that cardiac iron overload is infrequent and is less common than hepatic iron overload in heavily transfused patients with MDS [31–33]. The new GFM cardiac MRI study reported at ASH 2010 included a cohort of patients with a high median number of red cell units transfused (68 U), but so did the three previous studies: a median of 63 U in the 11‐patient United Kingdom study by Chacko et al, 90 U in the 10‐patient Israeli study by Konen et al, and 36 U in the 11‐MDS‐patient Chinese study by Au et al [31–33] It is notable that serum ferritin did not predict cardiac iron overload in any of these studies, which emphasizes the poor test characteristics of serum ferritin measurement.…”
Section: Discussionmentioning
confidence: 99%